Improving Concrete Underground Mining Pavements Performance Through the Synergic Effect of Silica Fume, Nanosilica, and Polypropylene Fibers - Saavedra-Flores, E; Avudaiappan-, S (Elsevier Ltd, 2021)
Concrete pavements for underground mining are in service under very aggressive exposure conditions (heavy loads and chemical attacks), which reduce their service life and affect mining productivity. Aiming to improve the concrete s performance, the combined use of silica fume, nanosilica, and polypropylene fibers was investigated. While each of these materials contributes independently to improving concrete performance, the similar chemistry of nanosilica and silica fume and the considerable workability loss by using each of these materials could negatively impact the concrete properties when used together. Therefore, it is necessary to demonstrate the synergy of using these three materials together, and quantify their relevance in the concrete response. In comparison to the control mix, the concrete mixes with the combined additions showed an average improvement of i) 17% of compressive strength, ii) 23% of splitting strength, and iii) 22% of flexural strength, iv) 200% of the surface resistivity, v) 212% of the abrasion resistance, and vi) 158% of less sulfate expansion. As the numerical modelling of the results indicated a statistically significant interaction between the independent variables, it is proposed that the silica fume, nanosilica, and fibers act synergically, enhancing the underground mining pavements. © 2021 Elsevier Ltd